2006
DOI: 10.3122/jabfm.19.5.517
|View full text |Cite
|
Sign up to set email alerts
|

Tenderness Over the Hyoid Bone Can Indicate Epiglottitis in Adults

Abstract: Adult acute epiglottitis is a rare but life-threatening disease caused by obstruction of the airway. The symptoms and signs of this disease may be nonspecific without apparent airway compromise. We encountered 3 consecutive cases of adult patients with this disease in a single 5-month period in one physician's office. In all cases, physical examination revealed tenderness of the anterior neck over the hyoid bone. These observations assisted us in identifying this rare disease quickly. We suggest that tendernes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Other symptoms and signs include hoarse or muffled voice, tenderness over the hyoid bone, cervical adenopathy, fever, cough, and ear pain. [5]…”
Section: Discussionmentioning
confidence: 99%
“…Other symptoms and signs include hoarse or muffled voice, tenderness over the hyoid bone, cervical adenopathy, fever, cough, and ear pain. [5]…”
Section: Discussionmentioning
confidence: 99%
“…A few articles in the medical literature have shown a clear association between hyoid bone tenderness and various pathologies [1][2][3][4] ; however, none have looked at the correlation of this sign with abnormalities on flexible nasal laryngoscopy. It was first described by Brown 5 in 1954, as part of the hyoid bone syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…More recent articles have suggested that it is a useful clinical indicator for the early detection of epiglottitis in adults. 3,4 In this study, we aimed to compare the laryngoscopic findings of patients having hyoid tenderness against patients who presented to voice clinic without signs of hyoid tenderness. The primary outcome of the study is to assess if there is any association between hyoid tenderness and laryngeal pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, securing the airway is of utmost importance. In adults although the symptoms and signs of the disease may be non-specifi c, most cases can be managed conservatively yet the potential for sudden airway obstruction still exists [5]. Early recognition of acute epiglottitis is therefore of Symptoms like fever, sore throat, odynophagia, drooling of saliva, stridor, change of voice and shortness of breath were recorded.…”
Section: Introductionmentioning
confidence: 99%